Teacher competency development model of higher vocational schools in Shandong province, China - Bian, Xiaoshu; Siththada, Thada (Edelweiss Applied Science and Technology, 2024)
Teacher competency is fundamental to successful vocational education reforms and quality enhancement. The rapid economic transformation and industrial upgrading in Shandong Province require highly skilled talents, prompting the implementation of modern vocational education (MVE) reform. However, the current competency of vocational teachers (VTs) often falls short of MVE standards, and there is an urgent need for a development model suitable for regional characteristics as a guide. In this study, we aim to assess the current state of VT competency development in Shandong Province and propose an integrated competency development model tailored to its specific needs. Our research employed a mixed-methods design, incorporating a cross-sectional survey of 280 VTs and 140 administrators and semi-structured interviews with management personnel. We conducted the exploratory factor analysis (EFA) on a comprehensive survey questionnaire and identified six key determinants of VT competency development. Based on these findings and expert interviews, we developed an integrated competency development model, comprising the teacher’s personal qualities and educational philosophy, educational technology competence, digital teaching competence, social policy, professional identity, and school culture and support. This model offers practical implications for designing effective teacher training programs and establishing supportive institutional environments, ultimately aiming to enhance the quality of vocational education through improved teacher competency.